Local Interstellar Spectra and Solar Modulation of Cosmic-Ray Proton and Helium - Cheng-Rui Zhu (The Astrophysical Journal)
Galactic cosmic rays suffer from solar modulation when they propagate through the heliosphere. The transfer of the local interstellar spectrum (LIS) to the top-of-atmosphere spectra is influenced by solar wind convection, and diffusion on the heliospheric magnetic field (HMF), among other factors. In this work, we derive the LIS of proton (p) and helium (He) covering energies from a few MeV/n to TeV/n, using a nonparameterization method. The study utilizes monthly AMS-02 data on proton and helium fluxes and their ratio to examine the evolution of solar modulation from 2011 May to 2017 May. To improve the fitting, the force-field approximation is modified by assigning different solar modulation potentials for high ( ϕ _h ) and low ( ϕ _l ) energy ranges. A sigmoid function is employed to describe the transition between these energy ranges. The analysis reveals that the break in proton and helium fluxes occurs at the same rigidity value, with a mean of approximately 6 GV and this break is more pronounced during the HMF reversal period. The ϕ _l is close to the result of Advanced Composition Explorer while the ϕ _h is close to the result of neutron monitor data. Furthermore, the long-term behavior of the proton-to-helium ratio ratio is found to naturally arise from the model when considering different Z / A values and the LISs for proton and helium.